Etiologia e controle biológico da doença pé-preto da videira - Santos, Ricardo Feliciano dos (2014)
Grapevines are one of the most cultivated fruits in the world, and many factors can affect its potential income and longevity, including pathogens attack. In 1990, black foot disease of grapevine began to worry producers and agronomists in various places of the planet where the crop was grown. Since 1999, plants with disease symptoms have been observed in Brazil. However, little is known about this disease in the southern region of the country. Thus, this study aimed to: 1) characterize isolates of the Ilyonectria spp. and Campylocarpon pseudofasciculare associated with black foot disease and study their pathogenicity; 2) evaluate Bacillus subtilis and Trichoderma spp. on the control in vitro and in vivo of Ilyonectria macrodidyma. For that, symptomatic plants were collected in georeferenced vineyards of Rio Grande do Sul. Isolation of the pathogen occurred from necrotic fragments of roots and crown for further study of the etiology and pathogenicity. In vitro tests (volatile metabolites and pairing of cultures) and in vivo (Vitis vinifera cv. Merlot grafted on Paulsen 1103) were performed to evaluate the control efficiency of Bacillus subtilis and Trichoderma spp., obtained from different commercial products, over Ilyonectria macrodidyma. Morphological characterization and multi-gene analysis of three regions (ITS, β-tubulin and histone H3) confirmed the existence of Ilyonectria macrodidyma, Ilyonectria robusta, "Cylindrocarpon" pauciseptatum and Campylocarpon pseudofasciculare associated with black foot disease. All 20 isolates were pathogenic to Vitis labrusca cv. Bordô, resulting in reduced mass of roots and shoots, roots and crown necrosis, vascular lesions, wilting of shoots and plant death. Bacillus subtilis and Trichoderma spp. were effective in inhibiting the mycelial growth of I. macrodidyma through volatile metabolites and pairing of culture tests.